PARTICIPATION OF ULTRA-PROCESSED FOODS IN BRAZILIAN SCHOOL CHILDREN'S DIET AND ASSOCIATED FACTORS - Arabele Teixeira de Lacerda; Ariene Silva do Carmo; Taciana Maia de Sousa; Luana Caroline dos Santos
ABSTRACT Objective: To evaluate the contribution of ultra-processed foods (UPF) in the schoolchildren diet and associated factors. Methods: Cross-sectional study with children from public schools in Southeast of Brazil, aged eight to 12 years old. A questionnaire was applied to the students to investigate anthropometric data, eating and lifestyle habits and food consumption. The consumption of UPF was evaluated by two 24-hour dietary recalls (24HR) of non-consecutive days, and the NOVA method was adopted for food classification. The sample was estimated considering the percentage of total caloric value from UPF identified by a similar study (n=260). The association between variables was evaluated by Simple and Multiple Logistic Regression. Results: The average energy consumption was 1992 kcal/day, 25.2% from UPF. Schoolchildren had a mean of 9.8±0.5 years of age, 53.4% were female and 32.6% were overweight. The most consumed UPF were industrialized pastas, sweet biscuits, sausages, chocolate powder and soft drinks. In the multivariate model, schoolchildren who have the habit of TV watching during meals and those with obesity presented 1.87 (95% confidence interval [95%CI] 1.03-3.39) and 2.05 (95%CI 1,01-4.20) times more chance of having higher consumption of ultra-processed foods, respectively. Conclusions: The contribution of UPF was expressive in the feeding of the students and it was positively associated with the excess of weight and with the habit of eating while watching television. These findings indicate the importance of nutritional interventions to promote healthy habits, thus preventing overweight during childhood.